2014
DOI: 10.1007/s11547-014-0394-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of systemic thrombolysis within 4.5 h from stroke symptom onset: a single-centre clinical and diffusion–perfusion 3T MRI study

Abstract: Treatment with IV rt-PA within 4.5 h of stroke onset preserves a significant amount of brain tissue from final infarction, and increases the possibility of early and late clinical improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…However, tPA therapy is beneficial only when given within a 3‐h window after the onset of a stroke and is associated with risk of hemorrhagic stroke when administered to older patients (Floris et al . ). Recent studies have indicated that tPA administration given beyond the traditional 3‐h window still has beneficial effects (Hacke et al .…”
mentioning
confidence: 97%
“…However, tPA therapy is beneficial only when given within a 3‐h window after the onset of a stroke and is associated with risk of hemorrhagic stroke when administered to older patients (Floris et al . ). Recent studies have indicated that tPA administration given beyond the traditional 3‐h window still has beneficial effects (Hacke et al .…”
mentioning
confidence: 97%